Relación entre el tipo de alimentación y anemia en lactantes de 6 meses de edad - Nuñez Marinovich, Manuel Antonio (2017)
To determine the relationship between feeding type and anemia in infants 6 months of age. MATERIAL Y METHODS: A descriptive observational and transversal study was done; the variables were type of milk consumed and presence or absence of anemia. RESULTS: There were 384 infants of 6 months of age, 200 (52%) presented anemia. The infants of 6 months of age who received exclusive breastfeeding (LME) were 204 (53%),mixed feeding (LM) were 178 (46%),and artificial feeding (LA) were only 2 children(1%), from these they had anemia 114 (55.8%) infants with LME; 85 (47.7%) infants with LM and 1 (50%) infant with LA, being the difference statistically significant between the 2 first ones. CONCLUSION: The anemia was more frequent in infants who received exclusive breastfeeding compared to those who received breastfeeding mixed and artificial feeding, there being a relationship between the type of lactation and anemia